Redefining “abandoned” agricultural land in the context of reforestation - Holl, Karen D.; Ashton, Mark S.; Bukoski, Jacob J.; Culbertson, Katherine A.; Curran, Sara R.; Harris, Thomas B.; Potts, Matthew D.; Valverde, Yesenia L.; Vincent, Jeffrey R. (Frontiers in Forests and Global Change, 2022)
Global mapping efforts to date have relied on vague and oversimplified definitions of “abandoned” agricultural land which results in overestimates of the land area that is likely to support persistent increases in forest cover and associated carbon sequestration. We propose a new conceptualization of abandoned agricultural land that incorporates changes in landholding status over time into determining whether land should be considered as abandoned. In order to develop more realistic estimates of the amount of land available for reforestation, we recommend clearly defining how abandoned land is categorized, discerning who owns and has rights to use the land, and combining remotely sensed data with household/stakeholder surveys to understand landowner motivations for not cropping or grazing land.